EDUCATIONAL MULTIMEDIA IN TEACHING VOCABULARY TO YOUNG LEARNERS OF ENGLISH: https://doi.org/10.5281/zenodo.20823380 - Liudmila , Polunina (Scientific practical conference, 2026)
This paper focuses on how advanced educational multimedia can enhance the vocabulary acquisition of young learners in English classroom. The analysis shows that a wide range of multimedia used by teachers at successive stages of vocabulary acquisition makes linguistic material more comprehensible through visual, audio, and situational supports as well as contributes to a reliable transfer of vocabulary from short-term to long-term memory.